The Local Wisdom of North Buton People in Flood Mitigation - Basri, La Ode Ali (Jurnal Ilmiah Peuradeun, 2021)
This study aimed to explain and to analyze the local wisdom of the North Buton people in flood disaster mitigation, namely worldview, traditional knowledge, norms, custom, and other traditions conducted by the people of North Buton in natural phenomena observation as the signs of floods, as well as efforts to reduce the risk of flooding by utilizing human resources and natural resources in the vicinity. The results showed that the people of North Buton have a set of local wisdom in flood mitigation which was inherited from their ancestors' legacy. It has been tested through empirical experience and also obtained the traditional legitimacy at North Buton people. That local wisdom included: (1) studying on the animal behavior namely the flock of Joremba (Dragonfly) which get into the residential area and the spooky sounds of Gara (Owl) birds at night, (2) construction of the houses on stilts or semi-permanent house behind the main house, (3) enacting the mamali (taboo) tradition in cutting down of the forests as a control mechanism in ecological balance creation to prevent erosion, (4) exploration of a new spring, (5) observation of the changes of the river volume and the discovery of the presence of the spring that appears suddenly in the rainy season.